1994
DOI: 10.1161/01.res.75.3.576
|View full text |Cite
|
Sign up to set email alerts
|

alpha 1-adrenergic agonists precondition rabbit ischemic myocardium independent of adenosine by direct activation of protein kinase C.

Abstract: Ischemit preconditioning in the rabbit is initiated by adenosine Al-receptor stimulation, which activates protein kinase C (PKC). Additionally, a,-adrenergic agonists can similarly protect ischemic myocardium, but there has been confusion about the role adenosine receptors play in this protection. To characterize the interaction between adrenergic and adenosine receptors and to study the possible role of PKC in this protection, we used isolated rabbit hearts perfused with oxygenated Krebs' buffer. All hearts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(97 citation statements)
references
References 45 publications
7
84
0
4
Order By: Relevance
“…Downey's group was the first to propose the hypothesis that activation of PKC plays a key role in the development of early PC against infarction (18)(19)(20). The PKC hypothesis of early PC has been supported by numerous investigations, which have demonstrated that various PKC blockers (i.e., H-7, staurosporine, chelerythrine, polymixin B) attenuate the protective effects of ischemic PC whereas PKC activators (i.e., PMA and 1-oleoyl 2-acetyl glycerol) mimic this protective effect in rabbits (23,(27)(28)(29), rats (21,24,25,30,33), dogs (31), and isolated rabbit cardiomyocyte preparations (22,32) as well as in isolated human atrial trabeculae (26). However, in contrast to the above studies, others have found that PKC inhibitors (H-7, staurosporine, bisindolylmaleimide, polymixin B) fail to block the protective effect of ischemic PC in dogs (35) and pigs (36,37).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Downey's group was the first to propose the hypothesis that activation of PKC plays a key role in the development of early PC against infarction (18)(19)(20). The PKC hypothesis of early PC has been supported by numerous investigations, which have demonstrated that various PKC blockers (i.e., H-7, staurosporine, chelerythrine, polymixin B) attenuate the protective effects of ischemic PC whereas PKC activators (i.e., PMA and 1-oleoyl 2-acetyl glycerol) mimic this protective effect in rabbits (23,(27)(28)(29), rats (21,24,25,30,33), dogs (31), and isolated rabbit cardiomyocyte preparations (22,32) as well as in isolated human atrial trabeculae (26). However, in contrast to the above studies, others have found that PKC inhibitors (H-7, staurosporine, bisindolylmaleimide, polymixin B) fail to block the protective effect of ischemic PC in dogs (35) and pigs (36,37).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies (5,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) indicate that protein kinase C (PKC), an ubiquitous intracellular mediator (34), may play an important role in the genesis of ischemic PC. However, no information is currently available as to whether PKC plays a role in late PC against myocardial stunning.…”
Section: Introductionmentioning
confidence: 99%
“…Hearts from anesthetized male Sprague-Dawley rats (225-250 g) were rapidly excised and cannulated onto the Langendorff perfusion apparatus using a protocol adapted from Tsuchida et al 36 The hearts were perfused with or without 50 nM TAT protein and subjected to I/R as described. 17 The Creatine Kinase (CK) activity in the coronary effluent was measured using a diagnostic kit (Stanbio Laboratory) and infarct size was measured using triphenyl tetrazolium staining.…”
Section: Methodsmentioning
confidence: 99%
“…Rat hearts were perfused in the Langendorff mode using a protocol adapted from Tsuchida et al (30). Hearts were perfused with Krebs-Ringer buffer at a constant pressure of 60 mmHg.…”
Section: Methodsmentioning
confidence: 99%